Educating and Leading: Managerial Efforts of Department Towards Superior Accreditation - Marbun, Rencan Carisma; Saragih, Ratna; Simanullang, Friska (LP. Ma'arif Janggan Magetan, 2022)
Accreditation is a form of assessment or evaluation of the quality and feasibility of an institution of a university or department carried out by an independent organization or body outside of higher education. The department is an academic implementing element that carries out professional education and if qualified can carry out academic education for undergraduate programs and/or postgraduate programs, in a section or one branch of science, technology and/or art. In order to maintain its quality, each department must carry out accreditation or reaccreditation continuously. The Pastoral Counseling Department was established in 2007 but until now the accreditation obtained by this department is still in the